(3MhGTi Ydi HgLI GdWdGHs - (3eMeO Hf bGSe GdhUdi GdYHOdis; (3eMeO Hf eMeO GdeZQHj GdQhGfjs ((3OeTb (B_ (3eOQSI GdHGPQGFi GdHZOGOi s)
(3ChdgG (B:s
(3jbhd eMeO Hf bGSe GdhUdi GdYHOdi GdMeO ddg GdPi QaY GdSeGA CeG HYO agPg MhGTi Ydi QSGdI GdESWQdGH GdeSeGg HHgLI GdWdGH s
(3BNQgG (B:s
(3EPG cGf GdYQV GdeWdhH hGdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai JeJ JPcQI CYdi GdCdHGH ai ESJjaGA GdYed HGdESWQdGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eOQSI GdMLjGJ (B_ (3GdehUd (B(66) s
Keywords: (3GdeLGejYs